Can selective quality education trigger new forms of poverty? (Journal of Parents and Teachers, 2026)
Unfortunately, throughout history, schools have reinforced mechanisms of exclusion towards the poor. Schools take for granted requirements that are non-existent in poor communities and families and inaccessible to them: parental support, tranquillity, comfort, serenity. In addition to this, it selects and ranks students, separating the “winners” from the “losers”. In order to implement a new policy, it is necessary to build dialogue, adapt structures and programmes, professionalise the actors involved and ensure the strong involvement of the people concerned.
Keywords: selective education, poverty, exclusion, new policy